RE-EXAMINING NOZICK’S EXPERIENCE MACHINE IN VIEW OF EMERGING AI COMPANIONS (Analele Universității București.Filosofie, 2024)
The aim of this paper is to examine Robert Nozick’s experience machine, assess where his thought experiment could have been framed differently or where it failed to consider other relevant aspects people view as important, such as their values and duties. Additionally, I provide what I consider to be a more fair test, still based on Nozick’s initial thought experiment, primarily changing the duration spent in theexperience machine and adding the option to lengthen the sessions according to one’s desires, together with preserving one’s memory of their actual lives, so as to accommodate the issues identified in Nozick’s original setting. In the second half of the paper, I correlate these findings with emerging AI technologies, which promise users companionship and constant support. Finally, the paper concludes that what matters is not what people think or say they will choose, but what they actually choose, calling for a need to lower one’s potentially deluded sense of self-control in relation to the kind of content we consume, especially online.